α-Klotho Expression in Mouse Tissues Following Acute Exhaustive Exercise - Rao, Zhijian; Zheng, Lifang; Huang, Hu; Feng, Yu; Shi, Rengfei (Frontiers in Physiology, 2019)
a-klotho, a multifunctional protein, has been demonstrated to protect against tissue from injury via anti-oxidation and anti-inflammatory. The expression of a-klotho is regulated by several physiological and pathological factors, including acute inflammatory stress, oxidative stress, hypertension, and chronical renal failure. Exhaustive exercise has been reported to result in tissue damage which is induced by inflammation, oxidative stress, and energy metabolism disturbance. However, little is known about the effect of exhaustive exercise on the expression of a-klotho in various tissues. To determine this, mice were exhaustively exercised by treadmill running, and sacrificed at different time point following exhaustive exercise. Our results confirmed that full-length (130KD) and shorter form (65KD) a-klotho primary expressed in the kidney. We determined that tissues that have been detected in this study (except for kidney and brain) mainly express shorter form a-klotho, even in the liver, shorter form a-klotho protein was detected which was previously reported do not express a-klotho, while the liver a-klotho mRNA was undetectable in this study. Furthermore, the shorter form a-klotho decreased immediately after acute exhaustive exercise, and then restore to the pre-exercise level or even higher in the next few days. Our results indicating that a-klotho may play a key role in the body exhaustion and recovery following exhaustive exercise.